Model of Religious Education and Moral Development in Special Detention Center for Children - Irawan, Feri; Marfiyanti, Marfiyanti; Arif, Armai; Zulherma, Zulherma (Khalifa Journal of Islamic Education, 2021)
The Child Special Detention Center is a place for fostering imprisonment-sentenced children. Children in prison have the right to receive guidance, coaching, supervision, assistance, education and training, and other rights under the provisions of laws and regulations. This study aims to describe how the model of moral development in the Special Detention Center for Children. This study uses a qualitative approach with a case study design approach, including data collection through observation, interviews, and documentation. Data sources were taken from several informants through an in-depth interview process and selected using the purposive sampling technique. The informants were employees and three children at the Child Special Detention Center who were previously involved in the moral education process and activities. The model of moral development for children in the Child Special Detention Center is as follows: i) providing motivation, guiding, and assisting children in practicing their worship. ii) providing a religious understanding through recitations. iii) providing formal and non-formal education, iv) providing lifeskills training. v) provisioning facilities and infrastructure for children's morals development. This research suggests the vital involvement of experts in moral development education at the Child Special Detention Center for Children. Also, this research is fundamental for initial reference to examine moral issues.